2021
DOI: 10.1111/cgf.142650
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Photo Editing on Smartphones via Intrinsic Decomposition

Abstract: Input (b) Tattoo (c) Glass (d) Mystique (e) Divine (f) CartoonFigure 1: Different types of effects produced with our mobile app. It is the first that supports a large variation of image manipulation tasks within a unified framework, which is based on intrinsic image decomposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
(84 reference statements)
0
7
0
1
Order By: Relevance
“…Our local consistency component comprising a convex combination of temporal neighbors can be seen as a crude form of local temporal denoising. Previously it has been shown that temporal denoising is effective in enforcing consistency [SST * 19]. We conjecture that efficient temporal denoising combined with flow‐based warping can further improve temporal stabilization not only for stylization but also for other tasks.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Our local consistency component comprising a convex combination of temporal neighbors can be seen as a crude form of local temporal denoising. Previously it has been shown that temporal denoising is effective in enforcing consistency [SST * 19]. We conjecture that efficient temporal denoising combined with flow‐based warping can further improve temporal stabilization not only for stylization but also for other tasks.…”
Section: Discussionmentioning
confidence: 76%
“…It was interesting to observe that for certain cases the method of Bonneel et al which degrades the processed style significantly was still preferred by users over others due to its high consistency quality. We also show subjective user preference for our method over the methods of Shekhar et al [SST * 19] and Thimonier et al [TDKP21] via another user study in the supplementary material. Shekhar et al which is completely based on temporal denoising is prone to introduce motion blur artifacts and is less efficient in terms of enforcing global consistency.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Selain itu, smartphone menyediakan aplikasi untuk editing foto yang jumlahnya lebih banyak dibandingan dengan kamera digital. Aplikasi ini dapat digunakan untuk mengedit foto yang dihasilkan oleh kamera smartphone, salah satu teknik editing yang digunakan adalah aplikasi Canva [4].…”
Section: Pendahuluanunclassified